(untitled) (Global Journal of Human-Social Science, 2018)
This paper examined the Boko Haram violence in northern Nigeria using the analytical lens of state failure through state-level analysis It also stressed that the socioeconomic and political grievances in the North-Eastern region of Nigeria do not only contribute to the operational success of Boko Haram but also to the continuing inability of the Nigerian state to deal with the challenge to ensure national prosperity effectively Having established that the current sectarian conflict in Nigeria is a factor of Nigeria state failure the government therefore needs to actively respond to the plight of its people Increasing rates of poverty and unemployment should be seriously addressed and more attention needs to be accorded to security issues in the country The government also needs to ensure adequate protection of domestic cultures and economies in the age of neo-liberal globalisation